Clinical and Histopathological Evaluation of Forty-one Cases of Pediatric Granuloma Annulare - Koku Aksu, Ayse Esra; İlhan Erdil, Dilara and Manav Baş , Vildan and Büşra Türk , Cemre and Leblebici, Cem and Tellal , Ebru Sarıkaya (Dermatology Practical & Conceptual, 2023)
Introduction: Granuloma annulare (GA) is a non-infectious granulomatous disease that can affect children and adults. Although many studies have been conducted adult GA patients, the literature on pediatric GA cases is limited. Objectives: Therefore, this study aimed to examine the demographic, clinical, and pathological features of pediatric GA cases. Methods: This study was performed retrospectively in a single-center tertiary dermatology hospital. Demographic characteristics and clinical and histopathological features were recorded. Results: Forty-one participants were included in this study, of which 66% were female. The mean age was 3.8 ± 2.6 years, and the mean lesion duration was 7.5 ± 10.3 months. The involvement of 78% of the patients was localized, and the remaining 22% was generalized. Asthma (30%) was the most common comorbid disease. Histopathological examination was performed on twenty-one patients, and the infiltrate pattern was interstitial in 71% of the cases and palisadic in 29%. Generalized distribution, trunk involvement, and concomitant disease tended to be higher in patients with an interstitial pattern than in those with a palisadic pattern. Conclusions: Atopy and asthma should be questioned in pediatric GA cases. There are differences between involvement, distribution, concomitant disease, and histopathological patterns, which may indicate differences in pathogenesis.